A case of recurrent Corynebacterium jeikeium endocarditis: Unanswered questions for the treatment of chronic endovascular infections. (2019) - Clarke, John-Ross D.; Abdur Rahman, Manal; Saul, Zane
Highlights: Many factors confer increased risk of recurrent endocarditis. Often many of these factors co-exist in the same host. There is always the risk of residual infected endocardial tissue despite repeated debridement. The traditional 4–6 week parenteral course in endocarditis accounts for bacterial tolerance and antimicrobial resistance. The decision on antimicrobial therapy and duration are supported by evidence but should be individualized. Abstract: A 53-year-old woman with end-stage renal impairment on hemodialysis was evaluated for recurrent episodes of Corynebacterium jeikeium bacteremia and endocarditis. Her recurrences occurred despite surgical debridement and extended courses of culture-directed antimicrobial therapy. The clinical course was complicated by the requirement of various endovascular prostheses for vascular access. To our knowledge this degree of relapse with guideline medical and surgical therapy is rare and challenges current practice and understanding of this group of infection.